Determination of fibre tension fracture toughness of composite laminates at high loading rate. (29th September 2022) - Cheng, Longfei; He, Rui; Gao, Yidi; Cui, Hao; Li, Yulong
Abstract: The dynamic fracture toughness of composite laminates in fibre tension failure mode is characterized here with compact tension (CT) sample, at loading rate of 25 m/s using bi-directional electromagnetic Hopkinson bars. Digital image correlation (DIC) with high-speed imaging is employed for obtaining the full-field strain fields. A dynamic J-integral method is proposed to analyse the dynamic fracture toughness, the kinetic energy and inertia effects involved in dynamic loading and crack propagation process has been analysed and calibrated. The fracture toughness of fibre tension failure at high loading rate is found to be about 25% lower than that in quasi-static load regime, and the R-curve effect under high loading rate is not significant than that in quasi-static load regime. It is suggested from X-ray CT and SEM images that the fibre pull-out length and size of failure process zone is reduced with increase in loading rate. Graphical abstract: Image 1 Highlights: Characterization of fibre tension fracture toughness at loading rate of around 25 m/s. Accurate and reliable calculation of dynamic J-integral, using high-speed imaging and digital image correlation. The fracture toughness for both crack initiation and propagation is found to decrease with loading rate.